Avaliação da qualidade dos cursos UAB sob a perspectiva dos alunos: uma proposta de modelo avaliativo de demanda - Costa Junior, Elizeu da Silva (2018)
The Federal University of Santa Maria (UFSM) is a participant in the Open University System of Brazil (UAB), in the offer of distance learning courses. The UAB system has gained strength and is seen as an effective public policy in the process of internalization of higher education. In this context, the need for excellence in the quality of processes and services provided to the community stands out. Among the processes, it is necessary to analyze demand for UAB courses. The aim of this research was to evaluate the quality of the courses offered by the Federal University of Santa Maria at the Open University of Brazil (UAB) and, later, to propose an instrument to support decision making in the demand assessment process. Therefore, the methodology used in the work was exploratory and descriptive of quantitative and qualitative character. Questionnaires were used, which were directed to the coordinators of the institutions of the UAB system, in the state of Rio Grande do Sul, and to the students of the UAB / UFSM courses in a regular situation in the second half of 2018. The method used brought important information which, translated into a feeling or believed in certain possibilities empirically. Statistical Package for Social Science (SPSS) was used for the statistical analysis of data and, in a complementary way, the Iramutec 0.7 alpha 2 software. It was also evaluated the profile of some cities- poles offered by the UAB / UFSM courses. It can be inferred that the student of the UAB system has a differentiated profile when compared to the classroom. When identifying and evaluating the quality of the services provided in the UAB/UFSM courses, in the most diverse dimensions, it is verified that, from the perspective of the students, there is the possibility of contributing to a better planning and performance of the supply and teaching process. Demand research, use of videoconferences as well as greater pedagogical accompaniment showed that these are the ways to improve the quality of service provision in the UAB/UFSM offer.